Analysis of relative nuclear DNA content in carnation (Dianthus caryophyllus) accessions reveals ploidy levels by flow cytometry - ANSAR, H; DHANANAJAYA, M V; TAJ, AMREEN; FAKRUDIN, B; REKHA, A; KUMAR, RAJIV; HALESH, G K (The Indian Journal of Agricultural Sciences, 2016)
Carnation (Dianthus caryophyllus L.) is one of the fifth most important ornamental species worldwide. Many desirable plant characteristics such as big size flower, adaptation to stress, and intra or interspecific hybridization capability are dependent on plant ploidy level. We optimized a quick flow cytometry method for DNA content determination in carnation accession samples that allowed a systematic evaluation of ploidy levels. To verify the actual ploidy levels, we counted chromosome numbers in the root tips of representative cultivar for each ploidy level. The relative nuclear DNA content was distributed into four kinds of discontinuous groups: 1.32 to 1.95 pg (group 1), 2.03 to 2.72 pg (group 2), 2.98 to 4.65 pg (group 3) and 5.33 pg (group 4) which might correspond to the following ploidy levels; diploid, triploid, tetraploid and hexaploid. The results showed that out of 60 carnation accessions, 33 were diploid, 5 were triploid, 21 were tetraploid and 1 was hexaploid.